PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PEMBANGUNAN - Quatro Thirtabrata, Audi; Rizki Windu Kencana, Ardhian; Desmawan, Deris (Universitas Maritim AMNI Semarang, 2022)
Human capital is an important factor in economic development. With quality capital, it is believed that economic performance will also be better. So it can be said that